FOLLOW-UP ANALYSIS RESULTS REPORT THE FINANCIAL TRANSACTION REPORTS AND ANALYSIS CENTER IN THE PROCESS OF INVESTIGATION IN MONEY LAUNDERING IN INDONESIA - Undang Prasetya Umara (Jurnal Hukum Replik, 2020)
Efforts to eradicate the crime of money laundering, Indonesia has an agency that specializes in reporting the possibility of money laundering and will conduct an analysis of suspicious financial transactions, namely the Financial Transaction Analysis Reporting Center. The report on the results of the Financial Transaction Analysis Reporting Center analysis should become a basic material that has value by law enforcers to carry out the process of preventing and eradicating money laundering in Indonesia, just like the Supreme Audit Agency of the Republic of Indonesia, where the Analysis Result Report can be used as the basis for the existence of state financial losses or potential loss to the country's economy. The highlight in this paper is the Follow-up to the Report on the Results of the Financial Transaction Analysis Reporting Center Analysis in the Investigation Process of Money Laundering in Indonesia. The approach method used is juridical normative, namely analytical descriptive legal research which is conducted by examining secondary data in the form of positive law literature in Indonesia and its implementation in practice. The results of the research will be analyzed qualitatively juridically, namely how to analyze the data obtained without using statistical formulas. The result of this research is that not all reports submitted by the PPATK to investigators are followed up by the investigators. The report on the results of the analysis that was not followed up by the investigator was a report on the results of the analysis which was of poor quality because there was no element of money laundering crime as well as the unclear identity of the customer (profile). Keywords: Financial Transaction Analysis Reporting Center, Investigation, Money Laundering